Ion−π Interactions in Ligand Design for Anions and Main Group Cations - Watt, Michelle M; Collins, Mary S; Johnson, Darren W (Accounts of chemical research, 2013)
Interactions between ions and aromatic rings are now a mainstay in the field of supramolecular chemistry. The prototypical cation−π interaction, first characterized in the gas phase, is now well-known as an important contributor to protein structure and enzyme function and as a noncovalent force found in many synthetic systems. The complementary “anion−π interaction”defined as an electrostatic attraction between an anion positioned over the centroid of an aromatic ringhas recently emerged as another reversible ion−π interaction in supramolecular systems. This type of interaction could offer new selectivity in binding poorly basic, strongly solvated anions and may also affect structure, biological function, and anion transport. This Account describes our group’s efforts in ion−π interactions in two areas. We first describe a series of self-assembled Group 15 (pnictogen)–thiolate complexes, all featuring prominent cation−π interactions between the trivalent pnictogen and an aromatic ring of the ligand. This structural feature appears to stabilize a variety of self-assembled dinuclear macrocycles, dinuclear M2L3 cryptand-analogues, and a tetranuclear As4L2 metallocyclophane. These complexes are all remarkably robust and feature intramolecular cation−π interactions, which suggest that these interactions could be an important feature in ligand design for the Group 15 elements. We also highlight our efforts to characterize the interaction between anions and electron-deficient aromatic rings in solution. Complementary crystallographic and computational studies suggest that off-center weak-σ interactions play the dominant role in stabilizing the anion–arene adducts unless an acidic CH bond is present to participate in favorable CH···anion hydrogen bonds. In solution the weak-σ complexes show downfield shifts of the proton resonances in their NMR spectra. With more polarizable anions such as bromide and iodide, we also observe anion binding by UV/vis spectroscopy. Initial solution studies suggest these reversible interactions are weak in organic solvents, but the Hofmeister bias in anion binding could be mitigated, if not reversed, in the halides using these anion−π type interactions.